Algoritma Reed Solomon Codes pada Sistem Informasi Pemanggilan Data Peserta Wisudawan-Wisudawati menggunakan QR Codes - Jumari Jumari; Fauziah Fauziah; Nur Hayati (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
This study aims to optimize the use of information systems for data management calling for graduates by using a QR code. At the analysis stage, it was found a problem that in calling the graduation participants still used the manual method, this caused the names of the graduates to be confused during the summoning procession. Based on the background of the problem, the researcher aims to make the calling process more efficient, replacing the system that uses QR code technology. The researcher uses the Reed Solomon method as error correction in the QR code Encoding process. This research was conducted through testing of 100 data and a total of 4000 times of testing including error correction, scan distance, and the condition of the card or paper. The results of the test are scans that are read in good condition with a correction level with distance testing of 6cm, 12cm, 18cm, 24cm and 30cm with errors L = 63.6%, M = 74%, Q = 79.8%, H = 93.8%while in damaged condition L = 42.8% ,M = 53.6% ,Q = 65.4%,H = 87.6%Therefore, this error fix affects the QR Code.